THE ROLE OF TRUTH AND RECONCILIATION COMMISSION IN PEACE BUILDING: NEPAL - Cottle, Drew; Thapa, Sunil (PEOPLE: International Journal of Social Sciences, 2017)
The ten-year Maoist insurgency in Nepal ended in 2006 with Comprehensive Peace Accord (CPA). A Truth and Reconciliation Commission (TRC) was established to address the human rights violations including societal impacts which occurred during the insurgency and to bring justice to its victims and perpetrators. Hence, this paper explores the role of the TRC in facilitating and establishing peace by analysing and comparing similar TRCs’ operations in South Africa, Liberia, and Sierra Leone. For this, the study utilizes primary information data collection methods and content analysis to critically examine the role of TRCs in the peace process. It identifies the key achievements of these previous TRCs and recommends ‘6R’ measures to Nepali TRC for justice and peace establishment in Nepal.